Absence of the spindle assembly checkpoint restores mitotic fidelity upon loss of sister chromatid cohesion - Silva, Rui (2018)
The fidelity of mitosis depends on cohesive forces that keep sister chromatids together. This is mediated by cohesin that embraces sister chromatid fibers from the time of their replication until the subsequent mitosis [1-3]. Cleavage of cohesin marks anaphase onset, where single chromatids are dragged to the poles by the mitotic spindle [4-6]. Cohesin cleavage should only occur when all chromosomes are properly bio-oriented to ensure equal genome distribution and prevent random chromosome segregation. Unscheduled loss of sister chromatid cohesion is prevented by a safeguard mechanism known as the spindle assembly checkpoint (SAC) [7, 8]. To identify specific conditions capable of restoring defects associated with cohesion loss, we screened for genes whose depletion modulates Drosophila wing development when sister chromatid cohesion is impaired. Cohesion deficiency was induced by knockdown of the acetyltransferase separation anxiety (San)/Naa50, a cohesin complex stabilizer [9-12]. Several genes whose function impacts wing development upon cohesion loss were identified. Surprisingly, knockdown of key SAC proteins, Mad2 and Mpsl, suppressed developmental defects associated with San depletion. SAC impairment upon cohesin removal, triggered by San depletion or artificial removal of the cohesin complex, prevented extensive genome shuffling, reduced segregation defects, and restored cell survival. This counterintuitive phenotypic suppression was caused by an intrinsic bias for efficient chromosome biorientation at mitotic entry, coupled with slow engagement of error-correction reactions. Thus, in contrast to SAC's role as a safeguard mechanism for mitotic fidelity, removal of this checkpoint alleviates mitotic errors when sister chromatid cohesion is compromised.